BMP2 is Required for Cephalic Neural Tube Closure in the Mouse - Castranio, Trisha (2009)
BMPs have been shown to play a role in neural tube development particularly as dorsalizing factors. To explore the possibility that BMP2 could play a role in the developing neural tube (NT) beyond the lethality of Bmp2 null embryos we created Bmp2 chimeras from Bmp2 null ES cells and WT blastocysts. Analysis of Bmp2 chimeras reveals NT defects at day 9.5 (E9.5). We found that exclusion of Bmp2 null ES cells from the dorsal NT did not always prevent defects. For further comparison, we used a Bmp2 mutant line in a mixed background. Phenotypes observed were similar to chimeras including open NT defects, postneurulation defects and abnormal neural ectoderm in heterozygous and homozygous null embryos demonstrating a pattern of dose dependent signaling. Our data exposes BMP2 as a unique player in the developing NT for dorsal patterning and identity and normal cephalic neural tube closure in a dose dependent manner.